Giardia intestinalis - atypical symptoms of infection in the daily practice of various specialists - Olszak, Joanna; Kapłan, Wojciech; Rachwał, Dominika; Piątek, Ewa; Zalewa, Karolina; Bartoszek, Lidia; Świdziński, Rafał; Skorupski, Bartosz; Lipiec, Jakub; Rogowska, Monika (Journal of Education, Health and Sport, 2023)
Giardia intestinalis infection is the most common parasitic infection in the world. The parasite's reservoir is mainly humans and many species of mammals. Giardiasis is a parasitic disease of the duodenum and small intestine. Infection spreads easily through the oral-fecal route. Its most frequent symptom is chronic diarrhea, but it can also be asymptomatic. This article analyzes atypical symptoms of Giardia Intestinalis infection based on available studies in the PubMed database. Observations have shown that giardiasis can manifest in various types of dermatoses such as urticaria, angioedema, atopic dermatitis, erythema nodosum, or Wells syndrome. A relationship between Giardia Intestinalis infection and various allergic syndromes, manifesting as chronic urticaria or angioedema, has also been observed, as well as an increased occurrence of food allergies due to increased exposure to antigens. Studies have also shown that giardiasis can cause polyneuropathy, avitaminosis, and malabsorption syndrome. Even years after infection, chronic fatigue syndrome can still be observed